MENGEMBANGKAN KEMAMPUAN MENGENAL HURUF ABJAD MELALUI PEMBELAJARAN MENGGUNAKAN MEDIA BULBINCA PADA ANAK-ANAK KELOMPOK A TK DARUT TAQWA KOTA KEDIRI - Novita Happy Nur Laili; Khan, Rosa Imani; Hanggara Budi Utomo; Lestariningrum (STPI Bina Insan Mulia Yogyakarta, 2024)
This research was motivated by the lack of development of the ability to recognize alphabet letters in group A children at Darut Taqwa Kindergarten, Kediri City, which was caused by a lack of tools or media for learning to recognize alphabet letters that were able to attract children's attention. The problem to be solved in this research is